Low-carbon neighborhood planning technology and indicator system. (May 2016) - Wang, Xiaoming; Zhao, Guochao; He, Chenchen; Wang, Xu; Peng, Wenjun
Abstract: Climate change has become a global issue influencing human survival and development while urban carbon emission is the main factor. As a fundamental building block of the city, neighborhood is not only the basic space to create a truly sustainable community but also the starting point for the use of low-carbon ideas and technologies to address climate change and promote the construction of a low-carbon city. Considering the significance of neighborhood planning on reducing carbon emissions, we proposed low-carbon neighborhood planning technologies from six aspects: layout planning, traffic planning, architecture planning and design, environment planning, municipal engineering planning and construction management. Moreover, we built an indicator system of low-carbon neighborhood based on these technologies from the perspective of "carbon source control" and "carbon sinks expansion" and used Analytic Network Process (ANP) to analyze the internal feedback and obtain the priorities. The system could be used to indicate low-carbon degree and provide measures for improvements. Furthermore, we carried out a case study using the proposed method for a neighborhood in Shandong province, China. Our practice has proved that the system could promote sustainable and low-carbon development of urban neighborhood and provide the government an effective tool.